UNIDADES FRASEOLÓGICAS ESPECIALIZADAS EVENTIVAS: NOVAS QUESTÕES SOBRE SEU RECONHECIMENTO EM CORPORA TEXTUAIS - Bevilacqua, Cleci Regina; Salgado, Ana Rachel; Silveira, Diônifer Alan da (Intercâmbio, 2010)
This work deals with difficulties met when recognizing Eventive Phraseological Specialized Units in a corpus of Brazilian environmental legislation. These units are characterized by an Eventive Nucleus (verb or a noun derived from a verb) and a Terminological Nucleus and by conveying knowledge concerning processes and actions of Environmental Law.